Advancing Quality of Life in a Turbulent World - Estes, Richard J.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2007)
World social development has arrived at a critical turning point. Economically advanced nations have made significant progress toward meeting the basic needs of their populations; however, the majority of developing countries have not. Problems of rapid population growth, failing economies, famine, environmental devastation, majority/minority group conflicts, involuntary population migration, increasing militarization, and other broadly-based social, political and economic forces are challenging the capacity of people to meet their most fundamental needs. For many, the conditions required to live a quality life are being eroded. The thirteen papers contained in this volume explore a broad range of factors that impact on quality of life worldwide-globalization, regionalization, recently regained political autonomy, population migration, factors that contribute to health and illness, shortages in food and agriculture, the importance of the family, community and sustainable development in promoting quality of life and, even more fundamentally, the contribution of faith and spirituality in advancing personal and collective well-being in an otherwise turbulent world.
Regional and National Perspectives on Advancing Quality of Life -- How Does European Union Enlargement Affect Social Cohesion? -- Promoting Well-Being: A British Perspective -- Importance and Satisfaction With Life Domains in Croatia: Representative Sample -- Advancing Quality of Life in Selected Sectors -- Commuting and Quality of Life: The Italian Case -- An Alternative Measure of Years of Healthy Life -- Analyzing "Sustainable Wealth" Indicators for Evaluating the Contribution of a Regional Industrial Sector Toward Quality of Life and Sustainable Development -- Fuel Sources and Well-Being in the Marshall Islands -- Spirituality as a Robust Empirical Predictor of Psychosocial Outcomes: A Cross-Cultural Analysis -- Hope and Spirituality in the Age of Anxiety -- Advancing Quality of Life for Selected Population Groups -- Communitarian versus Individualistic Arrangements in the Family: What and Whose Income Matters for Happiness? -- Socioeconomic Inequality and Inequalities in Health Among Kibbutz Elderly -- Life Satisfaction Crossover Among Couples -- Migrant Family Adaptation and Quality of Life: A Qualitative Study in Brazil.
Keywords: SOCIOLOGY; SOCIAL SCIENCES, GENERAL; SOCIOLOGY